Modelling the patient flow in an Out Patient Department (OPD) of a hospital using simulation techniques. Issue 1 (February 2021) - Kulkarni, S D; Roshni, V; Varshitha, S; Sandeep, M V; Monish, T; Venkataraman, V
Abstract: Hospitals are integral and vital entities of healthcare systems across the globe. Reduction of patient wait time is of utmost importance for the overall smooth functioning of any hospital. This paper discusses the analysis of the patient flow in the Out Patient Department (OPD) of a hospital. Data was collected with respect to patient arrival and service times in minutes. Input analyser was used to determine the distribution of the patient flow data collected at each section. A simulation model using Arena software was developed to study the patient flow in various sections of the OPD. The average waiting time and utilization of resources were determined for each sections. The results showed that there was a longer waiting time in billing section and Obstetrics and Gynaecology (OBG) section. Also there was high utilization of resources in these sections compared to the other sections of the OPD.